1998
DOI: 10.1046/j.1365-2567.1998.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin stimulates interleukin‐8 production by human lung fibroblasts

Abstract: SUMMARYBradykinin (BK ) is a potent inflammatory mediator that is generated from kininogens by the actions of plasma and tissue kallikreins. Lung fibroblasts have the potential to participate in the inflammatory responses by releasing proinflammatory cytokines in response to a variety of stimuli. We postulated that human lung fibroblasts might produce interleukin-8 (IL-8) in response to BK stimulation. The present study showed that BK stimulated human lung fibroblasts to produce IL-8 in a dose-and time-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…It has previously been shown that BK stimulated human lung fibroblasts to produce IL-8 by increasing its gene expression [11]. In the present study, it has been further demonstrated that BK at nM concentrations stimulated human lung fibroblasts to produce IL-6 and IL-8 in a dose-and time-dependent manner.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…It has previously been shown that BK stimulated human lung fibroblasts to produce IL-8 by increasing its gene expression [11]. In the present study, it has been further demonstrated that BK at nM concentrations stimulated human lung fibroblasts to produce IL-6 and IL-8 in a dose-and time-dependent manner.…”
Section: Discussionsupporting
confidence: 76%
“…Since the B2 receptor is a member of G protein-coupled receptor family, several steps are involved in the signal transduction leading to MAPK activation [30]. The authors recently reported that the stimulatory effect of BK on IL-8 production by lung fibroblasts is mediated, at least in part, via the PKC dependent pathway [11]. It has been reported that ERK 1/ 2 are enhanced via the PKC activation [31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations